(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Workplace accidents in food processing home industries can be triggered by unsafe worker behavior such as non-ergonomic work positions, not using personal protective equipment properly and not stretching muscles while working. The impact of unsafe behavior can cause health problems for workers, which can reduce worker productivity. Based on the results of a survey of PPN 47 students at one of the food processing home industries located in Sukamentri Village, Garut Regency, data was found that the implementation of the current occupational health program is still very lacking, marked by the lack of knowledge of home industry owners or workers regarding work accident prevention behavior. After data identification, problems were found with back and hand pain, worker body positions that were not in accordance with body ergonomics and incomplete use of APD. Workers said that the working position was standing for a long time and not using APD. Considering these conditions, it is necessary to increase worker knowledge, so that workers avoid work accidents. This increase in knowledge is carried out through Work Accident Prevention Behavior Training activities. The purpose of the activity is to increase worker knowledge in implementing work accident prevention behavior. The stages of the activity start from problem identification, social preparation and administrative preparation. Then continued with the implementation and evaluation stages of the activity. The results of the activity showed an increase in worker knowledge by 14.3 points. The average pretest score was 56.4 points and the average posttest score was 68.7 points. The activity ran smoothly according to the planned time. It is hoped that the training activities that have been implemented can be continued periodically by the home industry owners and Guntur Health Center.